Possibilities of using amantadines in the setting of the novel coronavirus infection in patients with Parkinson's disease - E. A. Katunina; Yu. N. Bezdolnyi; N. N. Shipilova (Неврология, нейропсихиатрия, психосоматика, 2021)
The novel coronavirus infection pandemic prompted not only the development of vaccines, but also the study of the effectiveness of already known drugs with antiviral activity. These drugs include adamantanes.Objective: to assess possible mechanisms of antiviral action of amantadine and memantine.Patients and methods. The study included 75 patients with Parkinson's disease (PD): 49 (65.3%) women and 26 (34.7%) men. The age of the patients ranged from 37 to 88 years (mean age: 65±7 years). The duration of the disease varied from 1 to 25 years (mean 12±7 years). Among the monitored PD patients, 22 (29.3%) had a novel coronavirus infection. Of 22 patients with coronavirus infection, 8 (36.4%) patients received adamantanes (four – amantadine sulfate, three – amantadine hydrochloride, one – memantine) in the complex therapy of PD for at least 3 months. On average, the duration of adamantane administration was 8±5 months.Results and discussion. PD patients who received adamantanes were less likely to develop COVID-19 than those who did not take adamantanes (p<0.05). At the same time, there were no significant differences in gender, age, duration of the disease and concomitant pathology in the com pared groups (p>0.05). Among patients who received adamantanes, the disease proceeded more easily, the number of cases of pneumonia was 3 times less (odds ratio 3; 95% confidence interval 0.44–20.3). In this group, no lethal outcomes were recorded, however, due to the small sample of patients, the differences between the groups were not statistically significant (÷2=1.99; p>0.05).Conclusion. The results of a retrospective study showed that the use of amantadine and memantine in patients with PD may have an effect on reducing morbidity and mortality in the novel coronavirus infection. This is consistent with published clinical observations suggesting a possible protective effect of amantadine and memantine against coronavirus infection.